2017
DOI: 10.5005/jp-journals-10005-1399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimicrobial Efficacy of Diode Laser, Triphala, and Sodium Hypochlorite in Primary Root Canals: A Randomized Controlled Trial

Abstract: AimTo evaluate the antimicrobial efficacy of diode laser, triphala, and sodium hypochlorite (NaOCl) against Enterococc-cus faecalis contaminated primary root canals.Materials and methodsForty-nine single-rooted human primary teeth were reduced up to cemento-enamel junction and biomechanically prepared. After sterilization, five teeth were selected as negative controls and remaining teeth were inoculated with E. faecalis. The teeth were then randomly divided into four groups. The first group was irradiated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
4
0
5
Order By: Relevance
“… 40 , 41 A study using human primary teeth ex vivo revealed that Triphala suspended in 10% DMSO (1:3) exhibited significant antibacterial activity compared with control as well as higher antibacterial activity compared with 3% NaOCl. 42 In vitro studies using Triphala ethanol extract have reported similar antimicrobial effects against E. faecalis compared with 2.5% NaOCl. 43 Thus, Triphala may represent a potential therapy to eliminate E. faecalis as more side-effects and larger risk are associated with NaOCl solution treatment.…”
Section: Therapeutic Uses and Studiesmentioning
confidence: 97%
“… 40 , 41 A study using human primary teeth ex vivo revealed that Triphala suspended in 10% DMSO (1:3) exhibited significant antibacterial activity compared with control as well as higher antibacterial activity compared with 3% NaOCl. 42 In vitro studies using Triphala ethanol extract have reported similar antimicrobial effects against E. faecalis compared with 2.5% NaOCl. 43 Thus, Triphala may represent a potential therapy to eliminate E. faecalis as more side-effects and larger risk are associated with NaOCl solution treatment.…”
Section: Therapeutic Uses and Studiesmentioning
confidence: 97%
“…The diode laser has a thermal photo disruptive action in dentin, which increases the root canal system's bactericidal effect. 24 Passive ultrasonic activation of the root canal irrigant is a predominant step in the endodontic treatment procedure. One of the main reasons that the activation of the irrigant is an essential step in the endodontic procedure is to create an acoustic streaming effect that enhances the wall shear stress and also it has a great role in distrust-ing the biofilm within the canal .Also, during irrigation ultrasonic creates a faster flow volume of the irrigant into the root canal, resulting in better debris and smear layer removal, less apical packing, and improved chemical product reaching to accessory canals and isthmuses.…”
Section: Discussionmentioning
confidence: 99%
“…The dried powders A. arabica (bark), T. Chebula (fruits), T. bellerica (fruits) and E. officinalis (fruits) plants have been used in traditional tooth powder formulation in India for more than 100 years (unpublished). Already many reports are available for the validation of numerous of potential benefits of these four plant material including anti-cariogenic properties [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] and these plant materials possess abundance of bioactive compound like quercetin, luteolin, saponins, anthraquinones, amino acids, fatty acids, various carbohydrates and polyphenols such as chebulinic acid which can exhibit the antimicrobial activities [34] , [35] . The above four plant materials used in this study having the potential to protect users against oral diseases, but this potential and the possible mechanism has not been investigated.…”
Section: Discussionmentioning
confidence: 99%